Hubungan Antara Kesadaran Diri dan Efikasi Diri Dengan Prokrastinasi Akademik Mahasiswa - Irawati, Dwi; , Dr. Taufik, M.Si (2015)
This study aims to determine the relationship between self-awareness and self-efficacy with academic procrastination. This research is quantitative. The population in this study were 394 students, research sample totaled 118 students by using simple random sampling technique. Measuring instruments used is a method of scale. Results: 1) There is a very significant negative correlation between self-awareness with academic procrastination, 2) There is a significant negative relationship between self-efficacy with academic procrastination, 3) There was a significant relationship between self-awareness and self-efficacy with academic procrastination, thus if the higher self awareness and self efficacy the lower level of academic procrastination and vice versa. Conclusions from these studies is that the self-awareness and self-efficacy together have a very significant negative correlation with academic procrastination. Research subjects have a high degree of self-awareness, self-efficacy and academic procrastination is classified as moderate. Implications for psychological science education that is the subject of the evaluation as well as the necessary role of psychology in the prevention effort among student academic procrastination.